2019
DOI: 10.1111/jvim.15511
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of complement deposition and opsonophagocytic killing of Rhodococcus equi mediated by poly‐N‐acetyl glucosamine hyperimmune plasma compared to commercial plasma products

Abstract: Background The bacterium Rhodococcus equi can cause severe pneumonia in foals. The absence of a licensed vaccine and limited effectiveness of commercial R. equi hyperimmune plasma (RE‐HIP) create a great need for improved prevention of this disease. Hypothesis Plasma hyperimmune to the capsular polysaccharide poly‐ N ‐acetyl glucosamine (PNAG) would be significantly more effective than RE‐H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…These results should be interpreted with caution, however, because this study was not designed to test the hypotheses either of superiority or of non-inferiority between these plasma products. Although in vitro data indicate PNAG HIP is superior to RE HIP for mediating killing of R. equi [32], the study reported here was not designed to compare protection between the 2 plasma types and our absence of evidence of a difference should not be construed as evidence of absence of an effect.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results should be interpreted with caution, however, because this study was not designed to test the hypotheses either of superiority or of non-inferiority between these plasma products. Although in vitro data indicate PNAG HIP is superior to RE HIP for mediating killing of R. equi [32], the study reported here was not designed to compare protection between the 2 plasma types and our absence of evidence of a difference should not be construed as evidence of absence of an effect.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to RE HIP, we recently demonstrated that transfusing foals between 12 to 24 hours after birth with plasma from donors hyperimmunized against the bacterial capsular polysaccharide β-1→6-poly-N-acetyl glucosamine (PNAG) prevented R. equi pneumonia following intra-bronchial infection at age ~28 days, whereas transfusion with commercial plasma from donor horses that were not hyperimmunized against either PNAG or R. equi and that had only background levels of antibody activity against PNAG and VapA failed to protect foals similarly infected [31]. Additionally, our laboratory has shown that PNAG HIP is superior to both RE HIP and standard plasma at mediating opsonophagocytic killing of R. equi by equine neutrophils [32]. Fixation of the complement component 1q (C'1q) to the PNAG antigen with vaccination-derived antibodies is considered essential to the functional activity of these antibodies both in vitro and within sera of foals receiving anti-PNAG antibodies via passive transfer from vaccinated dams [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that treating macrophages without the presence of epithelial cells is not sufficient to increase killing of R. equi 42 , and these cells were not present in our culture system where AMs were infected. Moreover, clearance of R. equi can be mediated by other innate immune cells including neutrophils 11,56,57 . We conclude that while nebulization with PUL-042 did not directly appear to impact killing of R. equi by AMs, it modulated immune Broncho-alveolar lavage was performed pre-(day 2 after birth) and post-nebulization (day 22, 1 day after the last nebulization): AMs were infected with virulent R. equi using a multiplicity of infection of 10 bacteria per macrophage (infected) or kept in media only (uninfected).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our laboratory has shown that PNAG HIP is superior to both RE HIP and standard plasma at mediating opsonophagocytic killing of R . equi by equine neutrophils [ 32 ]. Fixation of the complement component 1q (C’1q) to the PNAG antigen with vaccination-derived antibodies is considered essential to the functional activity of these antibodies both in vitro and within sera of foals receiving anti-PNAG antibodies via passive transfer from vaccinated dams [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%